Technical Efficiency of Shallot Production Inputs in Sumbersewu Village, Muncar District, Banyuwangi Regency: Efisiensi Teknis Input Produksi Bawang Merah di Desa Sumbersewu, Kecamatan Muncar, Kabupaten Banyuwangi - Nuriah Yuliati; Aulia Maharani Setyowati Matseri; Gyska Indah Harya; Rinda Lestari Rahayu (Jurnal Ilmiah Manajemen Agribisnis, 2026)
The efficiency of shallot farming is influenced by input management and increases in production factor prices. This study aims to analyze the effect of input use (land, labor, seeds, fertilizers, herbicides, and insecticides) on production and measure the level of technical efficiency of farmers. A survey method was used with 40 respondents in Sumbersewu Village, Muncar District, analyzed using the Cobb-Douglas production function and the Stochastic Production Frontier approach. The results showed that production was significantly influenced by land area, organic fertilizer, labor, NPK fertilizer, and insecticides. In contrast, seeds, SP36 fertilizer, KCL, and herbicides did not have a significant effect. The average level of technical efficiency of farmers reached 89.98%, indicating that there is still an opportunity to increase production by 10.02% through input optimization.